USING MEDIA TO TEACH DIFFERENT LEARNING STYLE IN X AND XII GRADE OF VOCATIONAL SCHOOL OF MEDICAL NUSANTARA PAMEKASAN - elly imrotul khulufiah (IJET (Indonesian Journal of English Teaching), 2018)
The purpose of this article is knowing the use of media to teach different learning style of student in Vocational School of Medical Nusantara Pamekasan. In this article, the researcher got the data by doing direct interview with one of the English teacher in that school. Based on the data, this article explain about the use of media to teach students with differet learning style.